Pleural effusion due to concealed abdominal injury - Deshmukh, Namita; Prasad, VSV (Indian Journal of Case Reports, 2016)
An eleven-year-old boy presented with massive left sided pleural effusion after non-response to intercostal chest tube drainage and empirical anti-tubercular treatment. The pleural fluid was hemorrhagic, did not grow any organism, nor had any malignant cell. A raised amylase level was indicative of pancreatic origin of the effusion. He had no abdominal sign. He had also developed disseminated intravascular coagulation. On revisiting history, the boy could recollect blunt abdominal injury prior to the onset of the illness. Endoscopic retrograde cholangiopancreatography revealed ductal leak at the neck of the pancreas that was endoscopically sealed using a stent. This case highlights the importance of a thorough search into the etiology of hemorrhagic pleural effusion. The symptoms and signs of pancreatic injury may be subtle, and the former should be suspected in case of blunt abdominal trauma.